The Yanomami's´ traditional burial rituals and the state-imposed limitations due to the COVID-19 pandemic: A fundamental rights collision - Cavalcanti Linhares Lima, Erick; Gomes de Souza, Alcenir (Direito em Movimento, 2023)
Due to the Covid-19 pandemic, a Yanomami was contaminated and died. The Roraima state authorities imposed a series of restrictions on the release of the body, requiring immediate burial in the local cemetery to avoid the possible risk of mass contagion. Roraima's Health Secretary stated that the immune system of indigenous people is more sensitive to respiratory diseases and that Covid-19 infection in a tribal community could have devastating effects. The fact is that, in general, in Yanomami culture, the spirit of the dead will only be released from the body (and not perish with it) if proper funeral rituals are performed, which require, for example, cremating the body and then eating its ashes in porridge prepared especially for the occasion. Only when the village consumes this sacred mixture, called "ripu", is it guaranteed that the spirit of the deceased will rest. The deceased's relatives requested the body's release for transport to their village for the funeral ceremony preparations. They argued that it was not a question of discussing the absolute or relative meaning of life, health, or the risk of contagion, but of respect for the indigenous culture, which should require these rights to be guaranteed by the State as seen by the community and not from the point of view of the surrounding society. They support their claim in Article 231 of the Constitution of the Republic (respect for their social organization and traditions), in Article 7.1 of ILO Convention 169 (right to define their priorities), and in item 57 of Resolution 1/2020 of the Inter-American Commission on Human Rights on Pandemic (health care according to the culture of tribal peoples).